Epidemiology and outcomes of acute kidney injury in elderly chinese patients: a subgroup analysis from the EACH study. Issue 1 (December 2016) - Ge, Shuwang; Nie, Sheng; Liu, Zhangsuo; Chen, Chunbo; Zha, Yan; Qian, Jing; Liu, Bicheng; Teng, Siyuan; Xu, Anping; Bin, Wei; Xu, Xin; Xu, Gang
Abstract Background Information on acute kidney injury (AKI) in elderly hospitalized patients is limited. This study aims to assess the incidence, risk factors and outcomes of AKI in elderly Chinese patients. Method The Epidemiology of AKI in Chinese Hospitalized adults (EACH) study is a multicenter, retrospective cohort study conducted in nine regional central hospitals across China. Patients aged more than 65 years were selected from the EACH study for this analysis. A novel approach with adjustment for frequency of serum creatinine was used to estimate the incidence of AKI in elderly patients. In-hospital outcomes, including mortality, renal recovery, length of stay and daily cost of elderly patients, were analyzed and compared with outcomes in younger patients. Results Of 144, 232 adult patients in the EACH study, 42, 737 (29.63 %) patients were 65 years or older, including 9773 very elderly patients (≥80 years old). The incidence of AKI was 15.44 % in patients 65–79 years old (community-acquired (CA) AKI of 3.89 % and hospital-acquired (HA) AKI of 11.55 %) and 22.22 % in the very elderly group (CA-AKI of 6.58 % and HA-AKI of 15.64 %). The mortality rate of AKI was 10.3 % in patients aged from 65 to 80 and 19.6 % in patients older than 80 years. AKI incidence, in-hospital mortality, percentage of patients requiring dialysis and percentage without renal recovery were higher in elderly patients than in younger patients. Conclusion The incidence of AKI in elderly Chinese hospitalized patients is high, which becomes a substantial burden on medical care in China.